2008
DOI: 10.2478/s11756-008-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemocytes/coelomocytes DNA content in five marine invertebrates: cell cycles and genome sizes

Abstract: Abstract:The hemocytes/coelomocytes DNA content in five selected marine invertebrates (sea mouse Aphrodita aculeata, spiny crab Maja crispata, sea star Echinaster sepositus, sea urchin Paracentrotus lividus, and tunicate Phallusia mammillata) was investigated by flow cytometry. The cell cycle analyses identified sea mouse coelomocytes as proliferating cells and revealed that spiny crab hemocytes and sea urchin coelomocytes complete their division in the hemolymph and coelom, respectively. The genome sizes of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…We determined the values of ploidy for our two identified populations and have found that P2 cells have, approximately, twice more DNA content than P1 cells ( Figure 1C). A similar study carried out by Fafandel and collaborators (2008) (24) reported also the existence of two populations with diverse ploidy, in which the DNA content ratio between them was around 4. The authors suggested that some cells in the high-DNA population had probably engulfed other, unknown, nuclei.…”
Section: Coelomocyte Fractionation Using Flow Cytometrysupporting
confidence: 61%
See 1 more Smart Citation
“…We determined the values of ploidy for our two identified populations and have found that P2 cells have, approximately, twice more DNA content than P1 cells ( Figure 1C). A similar study carried out by Fafandel and collaborators (2008) (24) reported also the existence of two populations with diverse ploidy, in which the DNA content ratio between them was around 4. The authors suggested that some cells in the high-DNA population had probably engulfed other, unknown, nuclei.…”
Section: Coelomocyte Fractionation Using Flow Cytometrysupporting
confidence: 61%
“…Interestingly, Fafandel and collaborators (24) reported that in the red starfish Echinaster sepositus circulating coelomocytes do not go through mitotic divisions, suggesting that all coelomocytes originate from the coelomic epithelium and are, thus, post-mitotic once they enter in the fluid. Their results contradict ours, although it should be taken into account that the DNA intercalator used in these previous studies (DAPI) stains only (or mostly) dead cells; the reason why in our assays we decided to use PI instead, which binds DNA more extensively, either in dead or alive cells.…”
Section: Analysis Of the Cell Cyclementioning
confidence: 99%
“…So far, among 13 starfish species belonging to four families, Saotome et al (34) reported that the genome is packed into 44 diploid chromosomes (34). A similar study carried out by Fafandel et al (35) also reported the existence of two populations with diverse ploidy, in which the DNA content ratio between them was around 4:1. The authors suggested that some cells in the high-DNA population had probably engulfed other, unknown, nuclei.…”
Section: Do Coelomocytes Have Diverse Ploidies?mentioning
confidence: 86%
“…Inexplicably, Williamson (6) selectively refers to only half of these data and claims they are consistent with his prediction, but the prediction is easily shown to be false merely by including the other two data. In contrast to the relatively large genomes of the tunicates Ciona intestinalis (C ϭ 0.20 pg) (6) and Ascidia atra (0.16 pg), the genome of a third tunicate Phallusia mammillata is actually smaller (0.06 pg) (25) than that of the larvacean Oikopleura dioica (0.07 pg).…”
Section: Tunicates Have Genome Sizes Similar To Larvaceans and Did Nomentioning
confidence: 74%